THE IMPORTANCE OF TEMPERAMENT IN AN INDIVIDUAL'S ECONOMIC ORIENTATION (Web of Scientists and Scholars: Journal of Multidisciplinary Research, 2025)
As is known, temperament is a characteristic associated with higher nervous activity. It is present in every person, it is considered our individual psychological characteristics, and temperament affects all the characteristics of a person. At the same time, it also has a significant impact on the economic orientation of a person. In the study, which was studied under the topic "The importance of temperament in the economic orientation of a person", the relationship between a person's success in economic activity and his temperament characteristics is analyzed. Temperament is an innate psychophysiological characteristic of a person, which determines his behavior, decision-making process, stress resistance and relationships. Temperament is of great importance in the economic sphere, especially in such areas as finance, business and management.